Characterization of Lactic Acid Bacteria Isolated From the Gastrointestinal Tract of a Wild Boar as Potential Probiotics - Li, Miao; Wang, Yi; Cui, Hongyu; Li, Yongfeng; Sun, Yuan; Qiu, Hua-Ji (Frontiers in Veterinary Science, 2020)
Lactic acid bacteria (LAB) are major microorganisms used for probiotic purposes and prime parts of the human and mammalian gut microbiota, which exert important health promoting effects on the host. The present study aimed to valuate and compare the probiotic potential and safety evaluation of LAB strains isolated from gastrointestinal tract of a wild boar from Greater Khingan Mountains, China. Amongst all of the isolated LAB strains, five isolates identified as Lactobacillus mucosae, L. salivarius, Enterococcus hirae, E. durans, and E. faecium, were remarkably resistant to acid and bile salt. The probiotic characteristics (including adhesion capability, antimicrobial activities, autoaggregation, and coaggregation abilities), and safety properties (including hemolytic activity, antibiotic resistance, and absence/presence of virulence factors) were evaluated. The results showed that all of five isolates exhibited high adhesive potential, remarkable aggregation capacity, and antibacterial activities. Upon assessment of safety, these strains were negative for hemolytic activity and all tested virulence genes. This study revealed that these LAB isolates, especially M2-71, possess desirable probiotic properties and have great potentials for the development of feed additives for animals to promote health.